The influence of the synthetic food colourings tartrazine, allura red and indigo carmine on the body weight of Tenebrio molitor (Coleoptera, Tenebrionidae) larvae - Martynov, V. O.; Brygadyrenko, V. V. (Regulatory Mechanisms in Biosystems, 2018)
Substances for protecting plants often contain colourings, the impact of which on invertebrates has been studied insufficiently. The addition of food colourings in different concentrations to the diet of saprophage beetles can affect their metabolism, causing loss of body weight. In the experiment, we determined the impact of tartrazine, allura red and indigo carmine on the body weight of Tenebrio molitor Linnaeus, 1758 larvae. The substances were added to their fodder at five concentrations (1, 0.1, 0.01, 0.001 and 0.0001 g/kg of dry fodder) during a 21-day experiment. Statistically significant data on changes in the body weight of T. molitor larvae were received after adding 1 g/kg concentration of indigo carmine and 0.1 and 1 g/kg concentrations of tartrazine. In the other variants of the experiment, no statistically significant differences were determined. Tartrazine, allura red and indigo carmine cause decrease in the body weight of T. molitor larvae, depending on the concentration of the colouring. The toxic effect of synthetic food colourings on living organisms and the low number of studies devoted to such impact on insects indicate the relevance and necessity for further research in this sphere.